Quality evaluation of surimi and fish nuggets from Queen fish (Scomberoides commersonnianus) - Moosavi‐Nasab, Marzieh (Food Sci Nutr, 2019)
The purpose of this study was formulation and evaluation of physicochemical properties of fish and surimi nuggets prepared from Queen fish (Scomberiodes commersonnianus) during 90 days of storage. Chemical analysis showed that surimi nuggets contained less protein, fat, and ash due to washing steps during surimi preparation. The titratable acidity, peroxide, and TBA values for fish nuggets were significantly higher than surimi nuggets during frozen storage (p < .05). Moreover, the textural properties of the products exhibited more firmness of surimi nuggets before cooking compared with fish nuggets (p < .05) and more firmness of fish nuggets after cooking compared with surimi one (p < .05). Furthermore, surimi nuggets were lighter and had lower total bacterial counts rather than fish nuggets during frozen storage (p < .05). SDS‐PAGE of the samples during storage exhibited more intensity of the bands related to α‐actinin, actin, and β‐tropomyosin in surimi nuggets compared with that for fish nuggets. Moreover, the sensory evaluation showed that acceptability of surimi nuggets was more than that for fish nuggets after frozen storage. These results showed that surimi nuggets had higher quality indicators rather than fish nuggets.